4t+23=11t-2

Simple and best practice solution for 4t+23=11t-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4t+23=11t-2 equation:


Simplifying
4t + 23 = 11t + -2

Reorder the terms:
23 + 4t = 11t + -2

Reorder the terms:
23 + 4t = -2 + 11t

Solving
23 + 4t = -2 + 11t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-11t' to each side of the equation.
23 + 4t + -11t = -2 + 11t + -11t

Combine like terms: 4t + -11t = -7t
23 + -7t = -2 + 11t + -11t

Combine like terms: 11t + -11t = 0
23 + -7t = -2 + 0
23 + -7t = -2

Add '-23' to each side of the equation.
23 + -23 + -7t = -2 + -23

Combine like terms: 23 + -23 = 0
0 + -7t = -2 + -23
-7t = -2 + -23

Combine like terms: -2 + -23 = -25
-7t = -25

Divide each side by '-7'.
t = 3.571428571

Simplifying
t = 3.571428571

See similar equations:

| 9=3/4(-12x+36) | | 6x+8y=4.1 | | 2k=7k+15 | | z+50=z+10+4z | | 3x-4(5x+7)=-130 | | 95+75x=96 | | u=(-(-2.42)±√(〖(-2.42)〗^2-4(1)(-102.64)))/(2(1)) | | y=8E-05x+0.0002 | | 99+v=5300/10 | | -20(20+-x)=100 | | -21-18=-3 | | 1/2(4x-16)=2(2x-8) | | -20(20+-x)=200 | | 5x+3y(2x)=22 | | 6m+2n+9m+8n= | | 21-18=-3 | | -20(20+-x)=800 | | x-4=40 | | 38s-10=0 | | 4y^2-6y+8y^2-5y= | | -20x+4=6+2x | | (x+2)(x-3)=2 | | 1/4x-2/3=y | | 3(k+3)=6(k-4) | | -15--4= | | -16x+5=6+5x | | 2x-1/x-7 | | 38s-4-6=0 | | 2(4-3X)=5(2-X) | | -9h++12h= | | ln(4x+2)=2.8 | | 384-400x=-56x^2-x |

Equations solver categories